LEISHMANIASIS IN NORTHERN AND WESTERN AFRICA: A REVIEW - Albert, Kimutai; Kamau, Ngure Peter; Kiprotich, Tonui Willy; Muita, Gicheru Michael; Bonareri, Nyamwamu Lydia (African Journal of Infectious Diseases (AJID), 2009)
Leishmaniasis, one of the highly neglected diseases is currently a significant health problem in northern Africa with a rising concern in western Africa because of co-infection with the Human Immunodeficiency Virus (HIV). In this review, we present a summarized analysis of the epidemiology, infective species, parasites reservoirs, diagnosis, treatment and control measures of leishmaniasis in northern and western Africa region. In northern Africa, the disease is prevalent in Morocco, Algeria, Tunisia, Egypt and Libya. Comparatively, there are low prevalence rates of the disease in West African countries including Cameroon, Ghana, Burkina Faso, Niger, Mali, Nigeria and Senegal. In North Africa, visceral leishmaniasis (VL) is caused by L. infantum and transmitted by Phlebotomus perniciosus and P. longicuspis. On the other hand, cutaneous leishmaniasis (CL) is mainly caused by L. major and transmitted by P. papatasi, P. duboscqi and P. pedifer with L. infantum and L. tropica causing lower incidences of the disease. Notably, Algeria is one of the countries that constitute 90% of CL cases worldwide. In Western Africa; CL is caused by L. major while VL is caused by L. donovani. In these regions, zoonotic and anthroponotic cutaneous and visceral leishmaniasis is a health problem that should be addressed urgently